2013
DOI: 10.14233/ajchem.2013.15355
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Chemistry of Groundwater Near an Industrial Area, Northwest China

Abstract: Groundwater is a vital source of domestic, industrial, agricultural uses in arid areas where precipitation and fresh surface water are limited.With the rapid development of industry and population growth in developing countries like China, human activity induced groundwater over-exploitation and pollution have become more and more serious. It is reported that there are as many as 2.8 million wells in China 1 and the heavy groundwater extraction has caused many problems such as groundwater level drop, salt wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The groundwater classification on the basis of TDS and TH [14,31,58,59] in Tongchuan are as follows (Table 2): 35.4% and 64.6% of samples were hard water or very hard water; 47.9% were desirable and permissible for drinking; 95.8% were fresh water and 4.2% were brackish. In addition, the TH values of water are the measures of the dissolved Ca 2+ and Mg 2+ content, which are expressed in CaCO 3 mg/L and can be associated EC, which is normally twice the hardness for uncontaminated water [23,57]. Otherwise, if it is higher than that proportion, it provides information on the presence of components such as Na + , Cl − or SO 4…”
Section: Physicochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The groundwater classification on the basis of TDS and TH [14,31,58,59] in Tongchuan are as follows (Table 2): 35.4% and 64.6% of samples were hard water or very hard water; 47.9% were desirable and permissible for drinking; 95.8% were fresh water and 4.2% were brackish. In addition, the TH values of water are the measures of the dissolved Ca 2+ and Mg 2+ content, which are expressed in CaCO 3 mg/L and can be associated EC, which is normally twice the hardness for uncontaminated water [23,57]. Otherwise, if it is higher than that proportion, it provides information on the presence of components such as Na + , Cl − or SO 4…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…The increment of the population also leads to the expansion of cities and municipal waste that affect the groundwater quality through organic and inorganic contaminants [17][18][19][20]. Furthermore, industrialization is one of the most significant factors affecting groundwater quality through the effluents released into the nature [21][22][23][24]. Papazotos et al [25] Water 2021, 13, 3256 2 of 19 investigated the impact of water-rock and agricultural activities in the Psachna Basin (Greece) on groundwater quality and found that groundwater was strongly affected by the ultramafic geological environment with anthropogenic activities as revealed by high concentrations of Cr, Cr 6+ , and NO 3 − .…”
Section: Introductionmentioning
confidence: 99%